Naegleria fowleri-associated encephalitis in a cow from Costa Rica - Morales, Juan A. (2006)
Species of Naegleria, Acanthamoeba, and Balamuthia are soil amoebae that can cause encephalitis in animals and humans. Of these, Naegleria fowleri is the cause of often fatal primary meningoencephalitis in humans. N. fowleri-associated encephalitis was diagnosed in a cow that was suspected to have rabies. Only formalin-fixed brain was available for diagnosis. There was severe meningoencephalitis involving all parts of the brain and numerous amoebic trophozoites were present in lesions. The amoebae reacted with N. fowleri-specific polyclonal antibodies in an indirect immunofluorescent antibody test. This is the first report of amoebic encephalitis in any host from Costa Rica.